A Simulation of Facility Layout Improvement at Local Food Industry - Suriansah, Nur Lyana Syahirah; Mahmood, Salwa; Samat, Muhammad Khairul; Jiran, Nur Syamimi (International Journal of Integrated Engineering, 2022)
As Salaiport become well known recently, demand for their product keep increasing. However, no proper layout of the workstation and the manual production process tend to reduce the production process and cause ergonomics problems. Simulation is a problem solving methodology for the solution of many real world problems, including to determine an effective layout for the workers in order to improve the productivity and efficiency of the production. The main aims of this study is to proposed a layout for Erul Food Industry that optimize processing time and minimize the cost in view of ergonomics. The Sketchup software is used to design the production line layout and the FlexSim software is used to identify the best design based on time and cost of processing. Based on the simulation results, Design 2 is the best design as it has minimum processing time and cost. It can be concluded that the shorter total running time of production, the lower cost of production.